Reversible Bonding of Thermoplastic Elastomers for Cell Patterning Applications - Byeong-Ui Moon (Processes, 2021)
In this paper, we present a simple, versatile method that creates patterns for cell migration studies using thermoplastic elastomer (TPE). The TPE material used here can be robustly, but reversibly, bonded to a variety of plastic substrates, allowing patterning of cultured cells in a microenvironment. We first examine the bonding strength of TPE to glass and polystyrene substrates and com-pare it to thermoset silicone-based PDMS under various conditions and demonstrate that the TPE can be strongly and reversibly bonded on commercially available polystyrene culture plates. In cell migration studies, cell patterns are templated around TPE features cored from a thin TPE film. We show that the significance of fibroblast cell growth with fetal bovine serum (FBS)-cell culture media compared to the cells cultured without FBS, analyzed over two days of cell culture. This simple approach allows us to generate cell patterns without harsh manipulations like scratch assays and to avoid damaging the cells. We also confirm that the TPE material is non-toxic to cell growth and supports a high viability of fibroblasts and breast cancer cells. We anticipate this TPE-based patterning approach can be further utilized for many other cell patterning applications such as in cell-to-cell communication studies.